2021
DOI: 10.1088/1755-1315/830/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of 2019 Peat Fire in South Sumatra Conservation Area

Abstract: In 2019, Indonesia seasoned another haze disaster due to peat fires. In the South Sumatra province, fires occurred in most of the peatland areas. The research aims to identify peat fires that occur in protected forest areas in The South Sumatra. The boundary of the protected forest area is obtained from the Forest Department of South Sumatra Province. Meanwhile, the fire events in the study area were analyzed by the hotspot distributions data during the dry season 2019 (Juni-November). The identification of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In 2015 and 2019, there was an IOD+ event, which caused the daily average precipitation in 2015 to only be 1.64 mm/day and, in 2019, only 2.07 mm/day. Previous studies have shown that the Indo-Pacific climate modes, namely IOD and ENSO, have been linked to the deficit in precipitation observed across the Indonesian region [13,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015 and 2019, there was an IOD+ event, which caused the daily average precipitation in 2015 to only be 1.64 mm/day and, in 2019, only 2.07 mm/day. Previous studies have shown that the Indo-Pacific climate modes, namely IOD and ENSO, have been linked to the deficit in precipitation observed across the Indonesian region [13,38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the satellite passes over the same locations twice a day and at night, providing up-to-date data that are valuable for firefighting teams to swiftly identify and address fire incidents. NOAA satellite-derived hotspot data can be used for forecasting hotspots and smoke, detecting fire incidents, monitoring forest fires, and mapping fire vulnerability levels [10,38].…”
Section: Hotspotmentioning
confidence: 99%
“…Based on earlier research, the IOD was compared to a threshold value of the annual DMI mean. A value above 0.5°C indicated a positive IOD and less than -0.5°C indicated a negative IOD [13]. The flow of the methodology is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset developed is the Soil Moisture Active Passive (SMAP) Level 3 from soil moisture observations. The Enhanced SMAP Global soil moisture data provides at 10 km spatial resolution with the range of estimated minimum and maximum values are 0 and 25.39 mm, respectively [13,14].…”
Section: Datamentioning
confidence: 99%